2020
DOI: 10.3390/molecules25153540
|View full text |Cite
|
Sign up to set email alerts
|

New Series of Double-Modified Colchicine Derivatives: Synthesis, Cytotoxic Effect and Molecular Docking

Abstract: Colchicine is a well-known anticancer compound showing antimitotic effect on cells. Its high cytotoxic activity against different cancer cell lines has been demonstrated many times. In this paper we report the syntheses and spectroscopic analyses of novel colchicine derivatives obtained by structural modifications at C7 (carbon-nitrogen single bond) and C10 (methylamino group) positions. All the obtained compounds have been tested in vitro to determine their cytotoxicity toward A549, MCF-7, LoVo, LoVo/DX, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
(145 reference statements)
3
18
0
Order By: Relevance
“…The chemical shift of C7 carbon in the spectra of colchicine derivatives 5−43 can be found at approximately 63.0 ppm, similar to that in the spectrum of azide 4. The appearance of a characteristic singlet of aromatic protons H5′ in the region 7.40−8.27 ppm in the 1 H NMR spectra and the signal assigned to carbons C5′ in the range 120.2−124.9 ppm in the 13 C NMR spectra confirmed the formation of the triazole ring. The presence of esters, amides, or carbamates in derivatives 18−28, 29−36, and 37−43 was confirmed by the appearance of characteristic signals of a carbonyl group and proton of these moieties (Table S1 and NMR spectra).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The chemical shift of C7 carbon in the spectra of colchicine derivatives 5−43 can be found at approximately 63.0 ppm, similar to that in the spectrum of azide 4. The appearance of a characteristic singlet of aromatic protons H5′ in the region 7.40−8.27 ppm in the 1 H NMR spectra and the signal assigned to carbons C5′ in the range 120.2−124.9 ppm in the 13 C NMR spectra confirmed the formation of the triazole ring. The presence of esters, amides, or carbamates in derivatives 18−28, 29−36, and 37−43 was confirmed by the appearance of characteristic signals of a carbonyl group and proton of these moieties (Table S1 and NMR spectra).…”
Section: Resultsmentioning
confidence: 72%
“…In view of the above, 1,2,3-triazoles represent a promising scaffold in the search for compounds with biological properties improved over those of the starting substances in which they could replace and mimic a certain moiety. Therefore, continuing our research on modifications of 10-N-methylaminocolchicine at position C7, 13,14,38,39 and together with the reports on the cytotoxicity of colchicines with a triazole ring on C7 carbon (both those with simple substituents and more complex conjugates with ferrocenyl and ruthenocenyl), 40−43 we synthesized 7-azido-10-N-methylaminocolchicine 4 and obtained a series of 39 derivatives (5−43) containing 1,2,3-triazole core. It should be noted that the double-modified derivatives of colchicine with a triazole ring have not been previously described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COL is a natural alkaloid with a 6/7/7 tricyclic ring system, including a tropolone ring and a steric center at the C-7 position leading to an S -configuration of the chiral axis defined by the bond joining rings A and C [ 19 , 20 , 21 ]. A variety of studies have demonstrated the influence of structural modification of COL on its therapeutic effects [ 8 , 22 , 23 ]. It has also been found that the methoxyl groups on rings A and C are essential to maintain the cytotoxicity of COL.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, the planar structure of tropolone ring C and the hydrophobic methoxyl at C-10 greatly impacted COL analogues' activities by affecting their interaction with the relevant protein. Herein, a total of 13 COL analogues (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) were involved in molecular docking analysis to understand better how the modification on ring C would affect ZO-1-related intestinal injury toxicity of COL. Chemically, these ligands with a type II structure, as shown in Figure 1, were all obtained from chemical modification at C-10.…”
Section: Effect Of Modification On Ring Cmentioning
confidence: 99%